Sounding identity in the digital age: Eastern Indonesia’s musical voices on Tiktok - Ismail, Ahmad (Frontiers in Communication, 2025)
This article investigates the mediation, circulation, and reframing of musical expressions from Eastern Indonesia—specifically Papua and Maluku—through the digital platform TikTok. Historically marginalized within Indonesia’s national cultural narrative, these regions have gained renewed visibility through the platform’s participatory and algorithmic dynamics. By conducting an interpretive analysis of viral songs such as “Aku Papua,” “Nyong Timur,” “Stecu-Stecu,” and “Pica-Pica,” etc., the essay examines how lyrics, bodily performances, and sonic aesthetics serve as modes of cultural affirmation and resistance. Drawing on theoretical insights from ethnomusicology, platform studies, and postcolonial critique, it posits that TikTok functions not only as a site of creative production but also as a stage for identity negotiation, where users transform regional vernaculars into shared digital narratives. While the platform provides visibility and symbolic inclusion, it also imposes constraints that risk commodifying identity. The paper advocates for an interdisciplinary engagement with ethnomusicology and digital anthropology to better comprehend how peripherally situated creators navigate algorithmic publics. Ultimately, this study positions music as a potent medium through which Eastern Indonesians assert presence, reconfigure representation, and contest cultural hierarchies in the digital age.